2017
DOI: 10.1021/acs.langmuir.7b02394
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Bone-like Hydroxyapatite by Mineralization on Supramolecular Porous Fiber Networks

Abstract: Hydroxyapatite (HA), the main inorganic component of bone tissue, is mineralized with collagen fibril scaffolds during bone formation. Inspired by the process, a self-assembled porous network architecture was designed and synthesized by using the 2-ureido-4[1H]-pyrimidone (UPy) modified glycerol molecule UPy-Gly, which was further utilized as a template for biomimetic mineralization. When incubated in simulated body fluid (SBF), the HA nucleus first formed in the holes of the template by the induction of hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…Therefore, the formation of the nano-bre structure of UPy dimer could be explained by the mechanism we investigated previously that the UPyurethan moiety self-assembled into distinct nano-bres with the p-p interaction of the conjugated structure and the lateral hydrogen bonding formed between urethan. 48 The nanober hard domains of polymers 1 and 2 appeared more distinct and densely packed compared with the nano-bers of polymers 3-5. Fig.…”
Section: Synthesis Of the Supramolecular Polymers 1-5mentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, the formation of the nano-bre structure of UPy dimer could be explained by the mechanism we investigated previously that the UPyurethan moiety self-assembled into distinct nano-bres with the p-p interaction of the conjugated structure and the lateral hydrogen bonding formed between urethan. 48 The nanober hard domains of polymers 1 and 2 appeared more distinct and densely packed compared with the nano-bers of polymers 3-5. Fig.…”
Section: Synthesis Of the Supramolecular Polymers 1-5mentioning
confidence: 96%
“…As the simplest substitution group, the methyl has little steric hindrance which would give no hinder to the formation of the nano-bre stacks. 48 With the increase of the steric hindrance of the substitution group at sixposition, the distinct and well-dened boundary of the nano-bre structure gradually became vague ( Fig. 1c-e), which indicated that the degree of phase separation decreased dramatically.…”
Section: Synthesis Of the Supramolecular Polymers 1-5mentioning
confidence: 98%
“…However, the simplicity of experimental setup, low cost, the high porosity, and high interconnectivity of electrospun fibers makes them ideal tissue scaffolds [1417]. HA nanoparticles are incorporated into the polymer matrix either through biomineralization of pristine polymer fiber mats or coelectrospinning of the polymer and the HA nanoparticles [4, 18]. The incorporation of most calcium phosphate ceramics into polymer nanocomposite electrospun fibers involves coelectrospinning of polymer containing calcium and phosphate precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Porous polymeric structures as an extracellular matrix (ECM) analogue provide a spatial conformation and orientation to cells and permits nutrient transport, fulfilling a pivotal role in tissue engineering [1][2] . The control of porosity and pore shape is crucial for the polymeric membranes and scaffolds since the size of the pores directs the cell and nutrition transport through the scaffold 3 .…”
Section: Introductionmentioning
confidence: 99%